Pengembangan Perangkat Pembelajaran IPA SMP Berbasis Discovery Learning untuk Meningkatkan Motivasi dan Hasil Belajar - Widiastuti, Sri; Danial, Muhammad; Arsyad, Muhammad (Program Pasca Sarjana UNM, 2022)
The study is a development research aims 1) to find discovery learning-based junior high school science learning tools to increase students' motivation and learning outcomes, 2) to analyze the validity, practicality and effectiveness of discovery learning based junior high school science learning tools to increase students' motivation and learning outcomes. The development model used in this study refers to the 4D development model, which consists of several stages, namely defining, designing, development, and dissemination. The learning devices developed had been conducted through the validation stage by the validator and through trials, and had been revised by the developers to produce learning devices which are valid, practical, and effective. The results of the study reveal that (1) the expert’s validation of RPP is 3.30 with valid criteria, (2) the expert’s validation of BAPD is 3.24 with valid criteria, (3) the expert’s validation of LKPD is 3.51 with very valid criteria, and (4) the expert’s validation of THB is 3.35 with valid criteria. The learning devices are stated to be practical because the learning devices implementation is in fully implemented category with an average value of 3.58. The teacher’s response and students’ responses are in very positive category with 87.50% and 87.50%, respectively. The learning devices also meet the effectiveness value with the results of increasing the score of learning motivation from 69.04% to 82.04% and the learning outcomes meet effective criteria with a class completeness percentage of 85%.